Patriarchal norms limits women’s participation in voting activities a case study of district upper Chitral - Bibi Rahila; Abdul Jawad (Social Science Review Archives, 2025)
Research background: Despite making up half of the global population, women remain mostly underrepresented in decision-making roles. The women feel inspired to enter into the electoral politics and voting process to create a more balanced and equitable society for their peers. However, they face tremendous obstacles in their way because of patriarchal society and economic constraints. Women in these societies struggle harder and longer to compete with their male counterparts, as they dominate the political landscape. Research methodology: The current study was conducted in district upper Chitral of KPK. More specifically political constituency PK-1 was constituted the study area. As the selected universe for the current study was upper Chitral. The three UCs (UC Mastuj, UC Charun and UC Laspur) are purposively selected. Total house hold population of selected villages stands at 1855. The required sample size for the population of 1855 stands at 320. One village (Awi, Booni-2, and Mastuj) is selected from the designated UCs. Findings: The findings emphasize that highly significant association was found between Patriarchal expectations discourages women actively participate in political discussions, patriarchal norms leads to unequal political representation for women, Patriarchal norms limits women ability to freely express their political opinions and women’s participation in voting activities. Conclusion: Patriarchal norms significantly control women’s participation in voting activities both in positive and negative directions. The male superiority in rural communities though discouraged women’s participation in active political representation or free expression of political opinion, the women that had liberty to participate in voting activities felt pressure from their male family members to favor or disfavor a candidate.